The Effect of Learning Cycle 5E Model on the Scientific Literacy of 10th Grade Students - Ayu Muliana; A. Wahab Jufri; Syamsul Bahri (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to determine the effect of the Learning Cycle 5E model on the scientific literacy of tenth-grade students at SMA Negeri 2 Labuapi in 2024. This research employs a quasi-experimental design with Pre-Test and Post-Test Non-Equivalent Control-Group. The study population comprises 92 students divided into four classes (XA, XB, XC, XD). Random sampling was used to select two classes as the sample, totaling 44 students, with class XC as the experimental group and class XB as the control group. The instrument used was essay-type questions. Data on students’ scientific literacy were collected from the Pre-Test and Post-Test results in both classes and analyzed using the Mann-Whitney test at a 5% significance level with SPSS 16.0. The test results indicated a p value of <0.05 (0.024<0.05), suggesting that the Learning Cycle 5E model has a significant effect on students’ scientific literacy.